Disciplinary Thievery - Mason White (Oz, 2012)
Architectural history since the late 1960s seems best characterized by swings from the project of disciplinary autonomy to various forms of disciplinary transgression. This binary is perpetuated in the proposition, albeit simplistic and debatable, that autonomy is preoccupied with criticality, or the limits of the discipline’s interiority, while the project of transgression remains preoccupied with “the real,” or the discipline’s exteriority.